On groups, whose non-normal subgroups are either contranormal or core-free - Kurdachenko, L.A.; Pypka, A.A.; Subbotin, I.Ya. (Доповіді НАН України, 2020)
We investigate the influence of some natural types of subgroups on the structure of groups. A subgroup H of a group
G is called contranormal in G, if G = H^G. A subgroup H of a group G is called core-free in G, if CoreG(H) = 〈1〉.
We study the groups, in which every non-normal subgroup is either contranormal or core-free. In particular, we obtain
the structure of some monolithic and non-monolithic groups with this property. Досліджено вплив деяких типів підгруп на структуру груп. Підгрупу H групи G називаємо контранормаль ною в G, якщо G = H^G. Підгрупу H групи G називаємо вільною від ядра в G, якщо CoreG(H) = 〈1〉.
Вивчено групи, в яких кожна підгрупа або нормальна, або контранормальна, або вільна від ядра. Точніше,
одержано будову деяких монолітичних та немонолітичних груп з цією властивістю.